Implementasi Supply Chain Management Pada Toko Sandal Menggunakan Aplikasi Dolibarr (Studi Kasus : Kroya Shoes) - Damayanthi, Ni Luh Putu Ari Yunia; Putri, Gusti Agung Ayu; Mandenni, Ni Made Ika Marini (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 3 (2022): JITTER, Vol.3, No.3, December 2022, 2023)
Information technology is currently undergoing changed and developments so rapidly that many trading companies need technology to support business proceses. Kroya Shoes is small company that sell various model of sandals made from synthetic leather. Problem in carrying out inventory management, difficulties in Enterprise Resource Planning (ERP) and problem often occur in the Supply Chain Management (SCM) of the company. The company' s business processes are implemented into dolibarr open source software. The final stage of the research was carried out using UAT questionaire and calculating the level of satisfaction of Dolibarr aplication user's with a likert scale. Calculation results the results of the survey carried out where to produce an average value with the convenience aspect of 67,5%, the average percentage value with usability aspect was 91,5% so that the total percentage obtained  from all aspects was 79,5 % with a description of the score interpretation criteria, namely Good.